Double effect of ocean carbon sink trading and financial support: analysis based on BGG-DICE-DSGE model - Xu, Yao; Wei, Zhenhao; Xu, Longyu; Zhou, Gang (Frontiers in Marine Science, 2024)
Achieving carbon peak and neutral as scheduled requires joint efforts to reduce emissions and increase sinks. But in the long term, mitigating climate change requires the latter to play a greater role, in which achieving economic and environmental benefits through ocean carbon sink trading is an indispensable and important measure. Around the ocean carbon sink trading, this paper constructs an ‘Economic-Financial-Environmental’ analytical framework through the BGG-DICE-DSGE model, explores the heterogeneous impact of ocean carbon sink trading on macroeconomics and climate change by impulse response, examines the influencing factors by sensitivity analysis, and uses welfare analysis to explore further performance in financial markets. It is discovered that: (1) ocean carbon sink trading can mitigate climate change, boost social welfare, and reinforce even more under active fiscal and monetary policies and higher ocean output percentage. (2) As the main body of carbon sink trading, firms have a more active impact on economic and environmental systems than government. (3) The proportion of marine output value significantly impacts dual benefits. The efficiency of ocean carbon sinks has a significant impact on environmental benefits, while the related impact of carbon sink prices is weak. (4) Due to the financial accelerator effect, any decrease in output caused by exogenous shocks in the financial market compounds the loss of social welfare. This paper theoretically explains the strategic significance of ocean carbon sink trading, and provides necessary experience and reference for the establishment of ocean carbon sink trading market in the future.